PENINGKATAN KEMAMPUAN MENGENAL KONSEP DAN LAMBANG BILANGAN MENGGUNAKAN MEDIA PAPAN RABA PADA ANAK USIA 3-4 TAHUN DI PAUD INSAN PRESTASI SCHOOL - Puspadewi, Kadek (Education For All, 2023)
This research aims to improve the ability to recognize number symbols using a touch board in children aged 3 - 4 years at PAUD INSAN PRESTASI SCHOOL, Denpasar. This research is motivated by the low ability to recognize number symbols in children aged 3 - 4 years and learning activities to recognize number symbols only using LKA. This research is Classroom Action Research carried out in collaboration with teachers using the Kemmis and Mc Taggart model with stages of planning, implementation, observation and reflection. The research was carried out in October 2016. The research subjects were play group children (aged 3 - 4 years) consisting of 20 children consisting of 9 boys and 11 girls. The object of the research is the ability to recognize number symbols using a touch board. The data collection methods in this research are observation and documentation. Meanwhile, data analysis techniques use descriptive and quantitative. The average percentage of ability to recognize number symbols in pre-action was 58.82%, increased by 15.25% in cycle I to 74.075 and increased again by 18.09% in cycle II to 92.16%. This increase occurred because the learning steps using the touch board media were counting the number of objects, introducing number symbols with the touch board, showing number symbols on the touch board, touching the number symbols on the touch board, and pairing number symbols with objects. Keywords: Ability to recognize number symbols, touch board media, children aged 3 – 4 years